97 Improving End of Life Care Decision Making across North Wales. (14th March 2023) - Finlow, Charlie; Foster, Alison; Lewis-Williams, Gemma; Poolman, Marlise; Thomas, Ben
Abstract : Background/Introduction: Treatment and care towards the end of life (EoL) often involve decisions that are clinically complex and emotionally distressing. Patients' decision-making needs to be supported by appropriate, individual, timely discussions with clinicians and those important to them. In North Wales, the support for end of life decision-making (EoLDM) is fragmented and uncoordinated. Aim: We undertook a detailed exploration of EoLDM in North Wales to inform a quality improvement (QI) strategy. Method(s): We mapped components of EoLDM and examined those via individual and group interviews with stakeholders based on normalisation process theory constructs. We checked alignment with local and national guidance, contextualised findings utilising previous regional work, and prioritised QI topics. Results: Examination of EoLDM components (discussions, documentation, acting on decisions and governance) revealed well-known barriers (e.g. time constraints, lack of universal health care record) and key themes (e.g. need for clinician education & communication skills, executive leadership and dedicated people & systems resource). A targeted QI strategy includes coordinated communication 'do not attempt resuscitate' pathways between care settings, dedicated training resource for rolling clinician education, fit-for-purpose documentation of treatment escalation considerations and a public awareness campaign. Conclusion(s): The detailed exploration of EoLDM across the region has resulted in a targeted QI strategy. It acts as a springboard for future work to normalise EoLDM. Our vision is that everyone in North Wales can have discussions to support their EoL decision-making at the right time supported by skilled clinicians. Fit-for-purpose pathways and documentation should ensure decisions and preferences are acted upon, within a robust governance framework. Only by learning from one another have we been able to grow together for the people of North Wales.